2020
DOI: 10.1111/iwj.13505
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognosis of diabetic foot ulcers treated by an interdisciplinary team in Canada

Abstract: The aim of this study was to determine the wound healing outcomes of patients with a plantar diabetic foot ulcer (DFU) treated with an interdisciplinary team approach, and to identify associated variables. A retrospective observational cohort study of 140 adult patients, with a plantar DFU, treated between 2012 and 2018 at a wound care clinic of a University affiliated hospital was conducted. Predictive and explicative analyses were conducted with logistic multivariate methods and with a Receiver Operating Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…The wound care team continues to assess benchmarks on the national and peer hospital levels, modifying and improving protocols as necessary. The findings of this study are similar to other studies,28,29 demonstrating that the implementation of a comprehensive wound care team reduces the incidence of HAPIs and improves knowledge of care teams regarding management of these injuries. An example protocol and competency list are provided in Figures 11 and 12.…”
Section: Discussionsupporting
confidence: 89%
“…The wound care team continues to assess benchmarks on the national and peer hospital levels, modifying and improving protocols as necessary. The findings of this study are similar to other studies,28,29 demonstrating that the implementation of a comprehensive wound care team reduces the incidence of HAPIs and improves knowledge of care teams regarding management of these injuries. An example protocol and competency list are provided in Figures 11 and 12.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, in a study conducted with 140 patients, the authors found that only 18.6% of DFUs had healed at the four weeks of follow-up; 50.7% at the 3-month follow-up; and 77.9% at 1-year [41]. Although Patryś et al [42] study sample characteristics are similar to the sample analyzed in this study, it is difficult to compare healing rates between studies due to the wide variation in ulcer measurements, definitions, and characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…We include DFU (Wound, Ischaemia, and foot Infection—the WIfI classification grade I or higher or another classification system), VLU (C6 of Clinical‐Aetiology‐Anatomy‐Pathophysiology—the CEAP classification or other classification system that considers wound interruption in the skin barrier), lower extremity arterial disease (LEAD) with critical limb‐threatening ischaemia (CLTI) formerly designated by Critical Limb Ischaemia 18 (with an open wound, Rutherford classification 5 to 6, or Fontaine classification IV) and PU/I (category/stage 2 or higher of Pressure Injury Staging System). We consider DFU, VLU, CLTI and PU/I that do not heal or do not reduce 20 to 50% (<50% DFU, <40% VLU and 20–40% PU/I) in size in 4 weeks or 30 days with an appropriate treatment 4,19,20 …”
Section: Methodsmentioning
confidence: 99%
“…We consider DFU, VLU, CLTI and PU/I that do not heal or do not reduce 20 to 50% (<50% DFU, <40% VLU and 20-40% PU/I) in size in 4 weeks or 30 days with an appropriate treatment. 4,19,20 We assume healed wounds when the area is equal to 0 cm 2 , 0 mm 2 or complete epithelialization, although the FDA recommendation is "Complete wound closure is defined as skin reepithelialization without drainage or dressing requirements confirmed at two consecutive study visits 2 weeks apart", 16,21 but it was difficult to obtain this information in studies.…”
Section: Participantsmentioning
confidence: 99%